The Influence Of Store Environment, Product Quality Perception, Word Of Mouth, And Customer Experience On Purchasing Decisions For Mixue Ice Cream In Jambi City - Melisa Sebtiani; Syahmardi Yacob; Novita Sari (International Journal of Economic Research and Financial Accounting, 2025)
This study aims to analyze the influence of store atmosphere, product quality perception, word of mouth, and customer experience on purchasing decisions for Mixue Ice Cream in Jambi City. A quantitative approach was employed, using questionnaires distributed to 100 respondents. The data were analyzed using the Statistical Package for the Social Sciences (SPSS) version 29. The results show that the store atmosphere has no significant effect on purchasing decisions (t = 1.192, sig = 0.236). In contrast, product quality perception (t = 2.758, sig = 0.007), word of mouth (t = 2.928, sig = 0.004), and customer experience (t = 3.339, sig = 0.001) have a significant and positive influence on purchasing decisions. Simultaneously, all four variables jointly have a significant effect on purchasing decisions (F = 11.717, sig = 0.000), with an R² value of 0.324, indicating that 32.4% of the variance in purchasing decisions can be explained by the model. These findings suggest that experiential and relational factors play a more dominant role in influencing consumer purchasing behavior than physical store attributes. The study offers practical implications for businesses in optimizing marketing strategies focused on product quality, customer experience, and word of mouth to enhance consumer purchase decisions.